Artificial pollination, seed germination, and micropropagation of Coelogyne cristata and C. lawrenceana by in vitro protocol for conservation of endangered orchids - MUTHAB HUSSIEN; VLADIMIR A. KOVAL; ANDREY S. RYABCHENKO; SERGEY S. MAKAROV (Biodiversitas Journal of Biological Diversity, 2025)
Abstract. Hussien M, Koval VA, Ryabchenko AS, Makarov SS. 2025. Artificial pollination, seed germination, and micropropagation of Coelogyne cristata and C. lawrenceana by in vitro protocol for conservation of endangered orchids. Biodiversitas 26: 4384-4395. Coelogyne cristata and Coelogyne lawrenceana are rare and endangered orchids valued for their ornamental and medicinal uses. These species are severely threatened by low natural propagation rates and declining wild populations, making effective conservation strategies urgently necessary. However, a complete in vitro propagation system has not yet been established, further limiting their conservation. This study reports the first successful and efficient in vitro propagation protocol for both species, integrating artificial pollination, asymbiotic seed germination, and clonal micropropagation using low concentrations of Plant Growth Regulators (PGRs) combined with potato homogenate, coconut water, and banana homogenate to achieve this. Artificial pollination under greenhouse conditions achieved fruit set rates of 65% in C. cristata and 45% in C. lawrenceana, respectively. Seeds germinated at high frequencies on half-strength Murashige and Skoog (½ MS) medium: 98% in C. cristata with 0.5 mg L?¹ IAA and 92% in C. lawrenceana with 0.5 mg L?¹ 6-BAP. Optimal protocorm development occurred with 0.5 mg L?¹ meta-Topolin (mT) and banana homogenate for C. cristata and 0.5 mg L?¹ 6-BAP with coconut water for C. lawrenceana. The highest shoot multiplication was obtained in C. cristata (3.93±0.47 shoots/explant) using 0.5 mg L?¹ kinetin and potato homogenate, and in C. lawrenceana (6.28±0.15 shoots/explant) using 0.5 mg L?¹ mT and coconut water, both significantly higher than controls (p<0.05). Root induction was most effective in C. cristata with 1.0 mg L?¹ IBA or 0.5 mg L?¹ IAA plus coconut water, while C. lawrenceana rooted best with 0.5 mg L?¹ IAA. Acclimatized plants grown in a Sphagnum moss-charcoal-pine bark mixture (1:1:1) exhibited high survival rates: 87% for C. cristata and 82% for C. lawrenceana. This protocol offers a scalable solution for ex situ conservation and sustainable horticultural use of these threatened species.